From ‘creative cities’ to ‘urban creativity’? Space, creativity and governance in the contemporary city - Costa, P. (2012)
This paper derives from a broader research program studying the forms of governance associated with creative dynamics in cities (the “Creatcity” project) and draws on the first empirical results generated by the study following analysis of a set of exploratory interviews involving actors central to thinking and acting on the contemporary city (political decision makers, official structures and civil society) in the three metropolitan areas selected for the project: Lisbon (Portugal), São Paulo (Brazil) and Barcelona (Spain). Analysis of the responses sought to identify the different perspectives on the concepts of urban creativity and creative city and the relationship between creativity, vitality and competitivity within urban contexts while seeking to understand interviewee perspectives on the structural conditions necessary for the development of creativity in the city in terms of spatial/geographic configurations and the associated cultural ambiances and economic activities. In parallel, we aim to debate the means of fostering and supporting creativity in urban environments and discuss just which strategic policies and governance processes best achieve this.